2021
DOI: 10.1103/physrevb.104.235409
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength focusing by engineered power-flow conformal metamirrors

Abstract: Many advances in reflective metasurfaces have been made during the last few years, implementing efficient manipulations of wave fronts, especially for plane waves. Despite numerous solutions that have been developed throughout the years, a practical method to obtain subwavelength focusing without the generation of additional undesired scattering is a challenge to this day. In this paper, we introduce and discuss lossless reflectors for focusing incident waves into a point. The solution is based on the so-calle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…In our recent work [36], we have used this power flow-conformal mirror approach to realize subwavelength focusing, requiring that the desired reflected waves converge to a point (or to a line, in the two-dimensional case). However, in that case, the presence of a drain is required to absorb the power of the focused wave after convergence at the focal point.…”
Section: From Power Flow-conformal Anomalous Reflectors To Subwavelen...mentioning
confidence: 99%
“…In our recent work [36], we have used this power flow-conformal mirror approach to realize subwavelength focusing, requiring that the desired reflected waves converge to a point (or to a line, in the two-dimensional case). However, in that case, the presence of a drain is required to absorb the power of the focused wave after convergence at the focal point.…”
Section: From Power Flow-conformal Anomalous Reflectors To Subwavelen...mentioning
confidence: 99%
“…For example, prior works have shown that a sink can be made from a scatterer whose impedance is perfectly matched to that of a converging wave. [ 8 , 9 , 11 ] This approach requires that loss be introduced into the system. In the context of the scattering matrix formalism relating input and output energy channels, this can be understood as an example of coherent perfect absorption (CPA) with a single radiation channel.…”
Section: Introductionmentioning
confidence: 99%
“…With this feature, EM characteristics of the reflected wave can be engineered. Such control has been the object of several studies proposing novel absorbers [14], [15], retro-reflectors [16], optical mixers [17], focusing [18] and nonlinear devices [19].…”
Section: Introductionmentioning
confidence: 99%